2014
DOI: 10.2478/ffp-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of botanical antifeedants on Melolontha melolontha grub feeding on Scots pine roots

Abstract: The aim of the study was to evaluate the possibility of using botanic antifeedants to reduce the damage caused by Melolontha spp. grubs. To achieve the objective, the experiments were established in semi-field conditions to estimate the antifeedant activity of rutin, quercetin (flavonoids from buckwheat Fagopyrum esculentum) and an extract from black alder Alnus glutinosa leaves against Melolontha melolontha grubs. The grubs were placed individually in the pots with a soil in which 2 year old Pinus sylvestris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Nonetheless, the results obtained so far indicate weak effects of natural enemies on grub population numbers. Other studies were carried out on the effects of repellent plants, and the results obtained by Skrzecz et al (2014) and Sukovata et al (2015b) showed that brown mustard (Brassica juncea (L.) Czern.) had repellent effects on the youngest developmental stages of grubs (especially in the case of forest cockchafer Melolontha hippocastani).…”
Section: Other Issuesmentioning
confidence: 99%
“…Nonetheless, the results obtained so far indicate weak effects of natural enemies on grub population numbers. Other studies were carried out on the effects of repellent plants, and the results obtained by Skrzecz et al (2014) and Sukovata et al (2015b) showed that brown mustard (Brassica juncea (L.) Czern.) had repellent effects on the youngest developmental stages of grubs (especially in the case of forest cockchafer Melolontha hippocastani).…”
Section: Other Issuesmentioning
confidence: 99%
“…Raspberries are susceptible to pests and to diseases caused by various fungal infections. A serious problem in Poland are also soil pests, especially grubs, including larvae of the widely widespread herbivorous May bug ( Melolontha melolontha L.), a beetle from the Scarabaeidae family (Milenkovic and Stanisavljevic 2003 ; Totic 2014 ; Skrzecz et al 2014 ; Sukovata et al 2015 ). Other insects affecting raspberry crops are the raspberry beetle ( Byturus tomentosus De Geer), the two-spotted spider mite ( Tetranychus urticae Koch), and the blossom weevil ( Anthonomus rubi Herbst).…”
Section: Introductionmentioning
confidence: 99%
“…A serious problem in Poland are also soil pests, especially grubs, including larvae of the widely widespread herbivorous May bug (Melolontha melolontha L.), a beetle from the Scarabaeidae family (Milenkovic and Stanisavljevic 2003;Totic 2014;Skrzecz et al 2014;Sukovata et al 2015). Other insects affecting raspberry crops are the raspberry beetle (Byturus tomentosus De Geer), the twospotted spider mite (Tetranychus urticae Koch), and the blossom weevil (Anthonomus rubi Herbst).…”
Section: Raspberry Pests and Diseasesmentioning
confidence: 99%